Effective move of Polypyrrole/TiO2 hybrid nanocomposites on removal of methylene blue dye by photocatalytic activity - N. Dhachanamoorthi; K. Oviya; Sathish Sugumaran; P. Suresh; M. Parthibavarman; K. Jeshaa dharshini; M. Aishwarya (Chemical Physics Impact)
Polypyrrole (PPy) was synthesized effectively by chemical oxidative polymerization of pyrrole. Organic-inorganic hybrid materials PPy-TiO2 with different PPy weight percents were prepared by mechanical mixing, by using titanium oxide nanoparticles. The characterizations of PPy-TiO2 hybrid nanocomposites were analyzed by FTIR, UV–Vis, XRD, TGA & DSC and SEM & EDAX. Fourier transform infrared (FTIR) spectra and X-ray diffraction (XRD) were used to distinguish the structure of the attained PPy-TiO2 hybrid nanocomposites. UV–vis techniques are proved the polymerization of pyrrole monomer and the strong interaction between PPy and TiO2 nanoparticles. Thermogravimetric analyzer (TGA-DSC) curves revealed that TiO2 can decrease the weight loss of nanocomposite and increase the thermal stability of synthesized nanocomposites. The residual mass of the pure Pyy-36.51 %, PPy-TiO2 (25 %)-64.82 %, PPy-TiO2 (50 %)-60.82 %, PPy-TiO2 (75 %)-70.50 % and pure TiO2- 96.69 % nanocomposites at the residual temperature 497.80 °C. The morphology and molecular structure of the hybrid nanocomposite were characterized by scanning electron microscope & Energy dispersive X-ray analysis spectroscopy (SEM & EDAX). These characterization results confirmed the polymerization of pyrrole and the strong interaction between PPy and TiO2. The material with outstanding absorption capability that meet in optical application is the challenging way, thus the photocatalytic analysis of PPy-TiO2 hybrid nanocomposites is merely a admissible results. It is notably the favorable degradation efficiency of pure PPy, the PPy+TiO2 (25 % 50 % & 75 %) nanocomposites are 82 %, 66 %, 67 % and 53 % respectively.